2008
DOI: 10.1158/0008-5472.can-08-1419
|View full text |Cite
|
Sign up to set email alerts
|

Agglomerative Epigenetic Aberrations Are a Common Event in Human Breast Cancer

Abstract: Changes in DNA methylation patterns are a common characteristic of cancer cells. Recent studies suggest that DNA methylation affects not only discrete genes, but it can also affect large chromosomal regions, potentially leading to LRES. It is unclear whether such long-range epigenetic events are relatively rare or frequent occurrences in cancer. Here, we use a high-resolution promoter tiling array approach to analyze DNA methylation in breast cancer specimens and normal breast tissue to address this question. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
152
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(174 citation statements)
references
References 44 publications
(52 reference statements)
19
152
2
1
Order By: Relevance
“…2B); reintroduction of GnT-V cDNA into KO tumor cells significantly attenuated the expression of Pcdh␤ genes in these cells (Fig. 2C), supporting the hypothesis that differential expression of Pcdh␤ genes in GnT-V KO tumors was due to altered expression levels of GnT-V. A recent study has shown that Pcdh gene clusters, including the Pcdh␤ family, are expressed at lower levels in human breast cancer tissues than in normal tissues, and these lower expression levels were linked to human breast tumorigenesis (26). To confirm and extend the observation concerning the differential expression of the Pcdh␤ gene cluster in mouse mammary tumors after deletion of GnT-V, Pcdh␤ gene expression was measured in the human breast cancer cell line MDA-MB231 after knockdown of GnT-V by siRNA.…”
Section: Microarray Analysis Of Her-2-induced Mammary Tumors-supporting
confidence: 77%
See 2 more Smart Citations
“…2B); reintroduction of GnT-V cDNA into KO tumor cells significantly attenuated the expression of Pcdh␤ genes in these cells (Fig. 2C), supporting the hypothesis that differential expression of Pcdh␤ genes in GnT-V KO tumors was due to altered expression levels of GnT-V. A recent study has shown that Pcdh gene clusters, including the Pcdh␤ family, are expressed at lower levels in human breast cancer tissues than in normal tissues, and these lower expression levels were linked to human breast tumorigenesis (26). To confirm and extend the observation concerning the differential expression of the Pcdh␤ gene cluster in mouse mammary tumors after deletion of GnT-V, Pcdh␤ gene expression was measured in the human breast cancer cell line MDA-MB231 after knockdown of GnT-V by siRNA.…”
Section: Microarray Analysis Of Her-2-induced Mammary Tumors-supporting
confidence: 77%
“…As shown in Fig. 2D, three members of the human PCDH␤ cluster (PCDH␤3, PCDH␤6, and PCDH␤13), which were shown to be significantly down-regulated in human breast cancer tissues (26), were dramatically enhanced in MDA-MB231 cells with GnT-V knockdown, further confirming the ability of GnT-V expression levels to regulate the expression of the Pcdh␤ cluster during breast tumorigenesis.…”
Section: Microarray Analysis Of Her-2-induced Mammary Tumors-mentioning
confidence: 54%
See 1 more Smart Citation
“…There are now numerous methods available for determining CpG methylation status (for review, see Laird 2010), including methods focused at the level of CpG islands (Ponzielli et al 2008;Kaminsky et al 2009), individual promoters (Weber et al 2005(Weber et al , 2007Novak et al 2008), and, increasingly, genome-''scale'' (Meissner et al 2008;Gu et al 2010) and genome-wide methods, either at high (Lister et al 2009) or low resolution (Serre et al 2009;Ruike et al 2010). These later methods can be broadly classified into the following designations: reduced representation approaches that are based on methylation-sensitive (e.g., HELP) (Oda et al 2009) or specific (e.g., CHARM) (Irizarry et al 2008) restriction digestion (for review, see Jeddeloh et al 2008), affinity-based methods such as methyl-DNA immunoprecipitation (MeDIP) (Weber et al 2005(Weber et al , 2007Novak et al 2008) and methyl-CpG binding domain-based capture (MBDCap) (Rauch et al 2006(Rauch et al , 2008Serre et al 2009), and the more direct bisulphite treatment-based methods (Lister et al 2009); coupling of reduced representation and bisulphite treatment has now been demonstrated (Meissner et al 2008;Gu et al 2010), and other combinations are also possible.…”
mentioning
confidence: 99%
“…These later methods can be broadly classified into the following designations: reduced representation approaches that are based on methylation-sensitive (e.g., HELP) (Oda et al 2009) or specific (e.g., CHARM) (Irizarry et al 2008) restriction digestion (for review, see Jeddeloh et al 2008), affinity-based methods such as methyl-DNA immunoprecipitation (MeDIP) (Weber et al 2005(Weber et al , 2007Novak et al 2008) and methyl-CpG binding domain-based capture (MBDCap) (Rauch et al 2006(Rauch et al , 2008Serre et al 2009), and the more direct bisulphite treatment-based methods (Lister et al 2009); coupling of reduced representation and bisulphite treatment has now been demonstrated (Meissner et al 2008;Gu et al 2010), and other combinations are also possible. However, there are still many challenges involved in interpreting data from DNA methylation-based assays, due to complex effects, both technical and biological that are introduced at various steps in the procedure, in addition to implicit biases from the methods employed.…”
mentioning
confidence: 99%